Hubungan Kebiasaan Merokok dengan Kejadian Gagal Jantung Kongestif (GJK) - Najwa Khoirunnisa (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2026)
Introduction: Congestive Heart Failure (CHF) is an end stage clinical syndrome this is a major burden of cardiovascular morbidity and mortality in Indonesia. Although smoking is a known risk factor, primary evidence in Indonesia directly linking smoking exposure to the incidence of heart failure is still limited. This study aims to identify, critically evaluate, and systematically analyze all primary evidence in Indonesia (2020-2025) that assesses the quantitative relationship between smoking and the incidence of heart failure (HF) as well as related outcomes such as quality of life (QoL). Method: This study is a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. The search was conducted on five databases with a publication limit of 2020-2025. Only primary analytical studies that assessed the quantitative relationship between smoking and GJK or related outcomes were included. Discussion: Out of the initial 573 articles, 8 primary studies in Indonesia met the inclusion criteria. Evidence is divided into two main groups: (1) “direct relaionship” studies showing a strong risk signal between smoking and CHD (e.g. OR 4.868), and (2) “precursor pathway” studies consistently showing a relationship between smoking and hypertension and dyslipidemia (OR up to 6.067). Smoking history is also associated with a decline in quality of life in heart failure patients. Conclusion: Smoking exposure shows strong relationship with heart failure in the Indonesian population. However, the quantity and quality of direct priary evidence are still limited and dominated by cross sectional designs. Longitudinal cohort studies with objective biomarkers are needed to quantify the risk more accurately.